Nueva combinación en Bothriochloa Kuntze (Poaceae) - Scrivanti, Lidia Raquel (2011)
Bothriochloa laguroides var. torreyana (Steud.) M. Marchi & Longhi-Wagner (Poaceae: Andropogoneae), a taxon from South America, differs from the typical variety by several morphological characters and by differences in chemical composition. A new combination at specific rank is thus proposed for that species, Bothriochloa torreyana (Steud.) Scrivanti & Anton.